Performa Supply Chain Emping Melinjo di Kabupaten Bantul Daerah Istimewa Yogyakarta - Istiyanti, Eni; Kamardiani, Diah Rina (AGRARIS: Journal of Agribusiness and Rural Development Research, 2017)
Emping melinjo was one of the agroindustry-products that had great potential to be developed. The industry of emping melinjo contributed more on economic growth in the reason of creating jobs and alleviate poverty. The purpose of this study was to describe the performance of supply chain of emping melinjo from upstream to downstream and analyze the efficiency of supply chain of emping melinjo in Bantul regency. Field study to obtain primary data was done through interviews with the practitioners of emping melinjo supply chain (including farmers and merchants of melinjo as well as producers and retailers of melinjo chips). The results of field studies then tabulated and analyzed descriptively and quantitatively using Linear Programming. The analysis showed that there were 37 supply chain networks of emping melinjo in Bantul. The practitioners of upstream supply chain were melinjo farmers, middlemen, traders, wholesalers, and retailers, while in the downstream, were emping melinjo producers, traders, small traders, wholesalers, retailers and consumers. The activities of the doer of emping melinjo supply chain includes purchasing, sales, harvesting, packaging, packing, stripping, storage, loading and unloading, transporting, sorting and grading. The flow of products and money in the supply chain of emping melinjo run smoothly, while the flow of information was sluggish. Based on linear programming analysis the cost of supply chain of emping melinjo would reach minimum level at Rp33,969,264 per week if the production of emping melinjo as many as 25 361 kg per week wich was distributed using 22 networks.